Innovativ : Beispiele postinformeller Österreichischer Bildkunst. - Kulturhaus Graz (Graz : Kulturhaus, 1985)
Anzinger, Siegfried ; Attersee, Christian Ludwig ; Barek, Bernhard ; Bohatsch, Erwin ; Brus, Günter ; Frank, Heinz ; Gironcoli, Bruno ; Jascha, Johann ; Jungwirth, Martha ; Kappa-Kocherscheidt, Kurt ; Len, Ernst ; Messensee, Jürgen ; Nitsch, Hermann ; Xaver, Franz ; etc.
Innovativ : Beispiele postinformeller Österreichischer Bildkunst, Kulturhaus, Graz, 1985
boek